Method for crystallization of active pharmaceutical ingredients
Patent Information
- Application Number
- JP2024545883
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-05-30
- Filing Date
- 2024-01-18
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2044-01-18
Smart Images

Figure 2025508347000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to methods for crystallization of active pharmaceutical ingredients (APIs), and in particular to methods in which crystallization and crystal growth are controlled by aqueous solutions containing one or more polymers and / or copolymers. [Background technology]
[0002] Many active pharmaceutical ingredients (APIs) have limited bioavailability, mainly due to their insufficient dissolution rate to treat the target pathology. It is well known that the dissolution rate of an API depends on the available surface area. Particle size reduction of an API can be used to increase the surface area and dissolution rate. In addition, nanoization can increase the solubility. Therefore, particle size reduction of an API using micronization / nanoization technology is an effective approach to improve the bioavailability of an API.
[0003] Amorphous materials are known to have significantly higher solubility than the corresponding crystalline materials, making amorphization an attractive option. Unfortunately, amorphous APIs tend to crystallize during processing, storage, and administration, and thus the solubility advantage may be lost. One of the most common approaches to stabilizing amorphous drugs is to molecularly disperse the drug in a polymer matrix and form an amorphous solid dispersion (ASD). However, for stabilization, the ASD dose must contain a significant amount of polymer.
[0004] US Patent No. 5,999,333 discloses a method for preparing a submicron-sized API, comprising dissolving the API in a water-miscible first solvent to form a solution, mixing the solution in a second solvent containing a surface modifier to produce a presuspension liquid, and adding energy to the presuspension liquid by homogenization, counter-current homogenization, microfluidization, or sonication.
[0005] US Patent No. 5,399,633 discloses a method for crystallizing an API which involves rapidly adding a solution of the API in an organic solvent to an aqueous polymer solution.
[0006] US Patent No. 5,993,336 discloses a method for crystallizing an API, which comprises dispersing an amorphous API in an aqueous solution of polyvinylpyrrolidone (PVP), followed by processing in a media mill filled with polymeric grinding media until the average particle size of the API is about 200 nm.
[0007] US Pat. No. 5,399,633 discloses a method for crystallizing coarse API particles by milling in an aqueous solution of Pluronic F127 until the particle size is reduced to about 270 nm.
[0008] Non-Patent Document 1 discloses a method for forming crystalline nitrendipine nanoparticles. In this method, nitrendipine is dissolved in a solvent of polyethylene glycol (PEG) and acetone, and then precipitated from an aqueous solution of polyvinyl alcohol, hydroxypropyl methylcellulose (HPMC) or poloxamer. The particles initially formed were amorphous. Continuing the precipitation process, these particles were transformed into nano-sized crystals under conditions where the process was carried out at low temperatures.
[0009] However, there remains a need for additional methods for the preparation of active pharmaceutical ingredients with improved bioavailability. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] European Patent No. 1347747 [Patent Document 2] US Patent Application Publication No. 2005 / 202092 [Patent Document 3] U.S. Pat. No. 5,518,738 [Patent Document 4] US Patent Application Publication No. 2015 / 0125535 [Non-patent literature]
[0011] [Non-Patent Document 1] Xia et al., Pharm. Res. 2012, 29:158-169 Summary of the Invention
[0012] The present disclosure is based on the observation that when amorphous nano-sized active pharmaceutical ingredients (APIs) are contacted with an aqueous solution comprising one or more polymers and / or copolymers, a suspension is obtained comprising the nano-sized APIs in a crystalline form.
[0013] It is therefore an object of the present disclosure to provide a novel method for the crystallization of an active pharmaceutical ingredient (API), the method comprising: providing an amorphous nano-sized API; Providing an aqueous solution comprising one or more polymers and / or copolymers; and contacting the amorphous nano-sized API with an aqueous solution comprising one or more polymers and / or copolymers to form a mixture, wherein the content of the amorphous nano-sized API in the mixture is greater than the solubility of the amorphous nano-sized API in the aqueous solution comprising the one or more polymers and / or copolymers, thereby obtaining a suspension comprising the nano-sized API in a crystalline form. Includes.
[0014] Further aspects of the disclosure are set out in the accompanying dependent claims.
[0015] Illustrative and non-limiting embodiments of the present invention, both as to organization and method of operation, together with additional objects and advantages thereof, will best be understood from the following description of specific illustrative embodiments when read in connection with the accompanying drawings.
[0016] In this specification, the verbs "to comprise" and "to include" are used as open limitations that do not exclude or require the presence of any unrecited features. The features recited in the accompanying dependent claims are mutually freely combinable, unless otherwise expressly stated. Furthermore, it is to be understood that the use of "a" or "an" throughout this specification, i.e., the singular, does not exclude a plurality. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is an XRD diffractogram of nano-sized amorphous ezetimibe and nano-sized amorphous budesonide. [Diagram 2] Figure 2A is an SEM image of nano-sized amorphous ezetimibe. Figure 2B is an SEM image of nano-sized amorphous ezetimibe crystallized from water. Figure 2C is an SEM image of nano-sized amorphous ezetimibe crystallized from water containing 5 wt.-% PPVVA and 0.2 wt.-% SLS. The top image is an enlargement of the corresponding area in the bottom image indicated by the dashed rectangle. [Diagram 3] Figure 3 is an SEM image of a composition containing ceritinib nanocrystals and poloxamer 407 (dry suspension; ceritinib:poloxamer ratio 1:1; w / w). Scale bars are 1 μm and 400 nm. [Figure 4] FIG. 4 shows the crystallization of ezetimibe in a suspension containing 20 wt.-% aq. PVPVA (ezetimibe:PVPVA ratio 1:1; w / w) followed by XRD as a function of time. [Diagram 5] Figure 5 shows the results of crystallization of amorphous nano-sized ezetimibe as a function of PVPVA concentration. The ezetimibe concentration was 2 mg / mL and the suspension was mixed overnight before filtering and drying for SEM. A: 1 wt.-% PPVVA + 0.2 wt.-% SLS; B: 2.5 wt.-% PPVVA + 0.2 wt.-% SLS; C: 5 wt.-% PPVVA + 0.2 wt.-% SLS. The top figure is an enlargement of the area of the corresponding bottom figure indicated by the dashed rectangle. [Figure 6] Figure 6 shows XRD diffractograms of ezetimibe nanocrystals (filtered and dried 25 mg / mL suspension) from Figure 5. a: 1 wt.-% PPVVA + 0.2 wt.-% SLS; b: 2.5 wt.-% PPVVA + 0.2 wt.-% SLS; c: 5 wt.-% PPVVA + 0.2 wt.-% SLS; d: crystalline bulk ezetimibe. [Figure 7] 7 shows the results of crystallization of amorphous nano-sized budesonide as a function of HPMC concentration. Budesonide concentration was 25 mg / mL and the suspensions were mixed overnight before filtering and drying for SEM. A: 1 wt.-% HPMC + 0.2 wt.-% SLS; B: 2.5 wt.-% HPMC + 0.2 wt.-% SLS; C: 5 wt.-% HPMC + 0.2 wt.-% SLS. Top panel is an enlargement of the corresponding area in the bottom panel indicated by the dashed rectangle. [Figure 8] Figure 8 shows XRD diffractograms of the budesonide nanocrystals of Figure 7. a: 1 wt.-% HPMC + 0.2 wt.-% SLS; b: 2.5 wt.-% HPMC + 0.2 wt.-% SLS; c: 5 wt.-% HPMC + 0.2 wt.-% SLS. [Figure 9] Figure 9: XRD diffractograms of dried mixtures of PVPVA and nano-sized crystalline ezetimibe. a: immediately after drying; b: stored for 7 hours; c: stored for 14 hours; d: stored for 30 days; e: bulk ezetimibe. t=40°C, 75% relative humidity. [Figure 10] Figure 10: XRD diffractograms of dried mixtures of HPMC and nano-sized crystalline budesonide. a: immediately after drying; b: stored for 7 hours; c: stored for 14 hours; d: stored for 30 days; e: bulk budesonide. t=40°C, 75% relative humidity. [Figure 11] FIG. 11 shows SEM images of nano-sized Ceritinib composition in fresh state and after storage at room temperature for one month. [Figure 12] FIG. 12 shows A: FASSIF and B: SGF-FaSSIF dissolution of a: ezetimibe prepared according to the present disclosure and b: bulk ezetimibe. [Figure 13]FIG. 13 illustrates the permeability of a: ezetimibe prepared according to the present disclosure and b: bulk ezetimibe. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] As defined herein, a nano-sized API is comprised of particles with a Dv90 equal to or less than 1000 nm, i.e., a nano-sized API is comprised of particles with a diameter of 90% by volume less than 1000 nm. The particle size of the API can be between 10 nm and 1000 nm, e.g., between 10 nm and 200 nm, between 200 nm and 500 nm, or between 500 nm and 1000 nm. The preferred size of the nanoparticles can depend on the API and the application, so the size distribution can be adjusted as desired.
[0019] A suspension, as used herein, is a mixture of a solid (here, the API) suspended in a liquid (here, an aqueous solution containing one or more polymers and / or copolymers).
[0020] As defined herein, an aqueous solution is water containing one or more dissolved substances. The dissolved substances in an aqueous solution may be solids, gases, or other liquids.
[0021] Unless expressly stated otherwise, the term "active pharmaceutical ingredient, API" refers to the API, its non-salt form, its physiologically acceptable salts, co-crystals, polymorphs and / or solvates.
[0022] In one aspect, the present disclosure relates to a method for crystallization of an amorphous nano-sized active pharmaceutical ingredient (API), the method comprising: a) providing a solid amorphous nanosized API, preferably as a dry powder; b) providing an aqueous solution comprising one or more polymers and / or copolymers; and c) contacting the solid amorphous nano-sized API with an aqueous solution comprising one or more polymers and / or copolymers to form a mixture, wherein the content of the amorphous nano-sized API in the mixture is greater than the solubility of the amorphous nano-sized API in the aqueous solution comprising the one or more polymers and / or copolymers. Including, This results in a suspension containing the nano-sized API in crystalline form.
[0023] The grain size growth of the API is inhibited during crystallization, and the resulting particles remain nanoparticles. For example, if the average grain size of the amorphous API is about 40 nm, the average grain size of the API crystallized using the method of the present disclosure may be about 120 nm. Thus, although the grain size of the crystalline API may be larger than that of the amorphous API, the crystalline API of the present disclosure is still nano-sized, and the grain size typically does not grow more than 300%, preferably does not grow more than 100%, more preferably does not grow more than 50%, even more preferably does not grow more than 25%, and most preferably does not grow more than 10% during crystallization.
[0024] The content of amorphous nano-sized API in the mixture must be, for example, at least 10 times, preferably at least 50 times, more preferably at least 100 times, even more preferably at least 500 times higher than its solubility in the aqueous solution containing one or more polymers and / or copolymers to form a suspension.Thus, the amount of amorphous API required in the present method depends on its solubility.Solubility can be measured by any method known in the art.
[0025] Typically, the contacting is carried out at a temperature of 15 to 40°C, preferably 20 to 40°C, for example 30°C.
[0026] In a preferred embodiment, the contacting comprises mixing the suspension. Mixing is preferably carried out for at least 10 hours, more preferably at least 16 hours, even more preferably at least 24 hours. A relatively long mixing time is preferred to achieve complete wetting and good dispersion. Mixing can be carried out, for example, by shaking, stirring, or by using a spatula. Mixing and wetting can be promoted by ultrasound. However, high intensity ultrasound is not required. The ultrasound intensity is preferably 3 W / cm. 2 The following is the result.
[0027] If mixing is omitted, contacting is preferably carried out for at least 24 hours.
[0028] The ratio of API:polymer and / or copolymer is typically 10:1 to 1:10, more preferably 5:1 to 1:5, most preferably 5:1 to 1:1, e.g. 4:1, 3:1, 2:1 or 1:1, where the amount of API is calculated as mg / mL of suspension and the amount of polymer and / or copolymer is calculated as wt% of suspension. For example, 25 mg / mL of amorphous nano-sized ezetimibe with a 1:1 API:polymer and / or copolymer ratio produces the desired crystals in 24 hours at 20° C. The optimal API:polymer ratio depends on the polymer and API.
[0029] The one or more polymers and / or copolymers can be synthetic polymers or biopolymers. Illustrative examples of exemplary polymers and copolymers suitable for the present method include polyvinylpyrrolidone / vinyl acetate (PVPVA), polyvinyl acetate (PVA), polyvinylpyrrolidone (PVP), hydroxypropylmethylcellulose (HPMC), hypromellose succinate (HPMCAS), polyacrylic acid (PAA), polyethylene glycol (PEG), polyvinylcaprolactam (PVCL), poloxamer, poly(N-vinylcaprolactam)-poly(vinyl acetate)-poly(ethylene glycol) (Soluplus®), and any copolymers thereof. Proteins such as wheat protein can also be used.
[0030] Too high a polymer content may lead to slow crystal formation. The optimum polymer content is polymer dependent.
[0031] A preferred copolymer is PVPVA. The content of PVPVA in the aqueous solution is typically 0.2 to 50 wt. %, for example 0.2 to 40 wt. %, preferably 10 wt.-% to 45 wt.-%.
[0032] Another preferred polymer is HPMC. The content of HPMC in the aqueous solution is typically 0.2 to 5% by weight.
[0033] Yet another preferred polymer is poloxamer. The content of poloxamer in the aqueous solution is typically 0.2-40% by weight, preferably 1-20% by weight. The poloxamer is preferably selected from the group consisting of poloxamer 331, poloxamer 338, poloxamer 181, poloxamer 407, poloxamer 182, poloxamer 184, poloxamer 237, poloxamer 188, and poloxamer 124, and more preferably poloxamer 407.
[0034] Preferably, the one or more polymers and / or copolymers are sufficiently hydrophilic and sufficiently lipophilic to interact with the API.
[0035] In one embodiment, the one or more polymers and / or copolymers comprise or consist essentially of a copolymer derived from a first monomer and a second monomer, where the first monomer is more hydrophilic compared to the second monomer. Preferably, the first monomer in its neat state has a relative dipole moment that is at least 0.1 Debye, preferably at least 0.2 Debye, more preferably at least 0.3 Debye, and even more preferably at least 0.4 Debye greater than the dipole moment of the second monomer in its neat state.
[0036] Suitable APIs for the present method are typically selected from BSC Class II APIs and BSC Class IV APIs.
[0037] Exemplary APIs suitable for the present disclosure include adefovir, dipivoxil, apalutamide, atazanavir, avacopan, deucravacitinib, doravirine, enzalutamide, elagolix, encorafenib, etravirine, everolimus, and cefovir. mus), etonogestrel, fenofibrate, glecaprevir, pibrentasvir, grazoprevir, pibrentasvir, griseofulvin, telmisartan, itraconazole, ivacaftor, lumacaftor, Tezacaftor, elexacaftor, lonafarnib, nabilone, olaparib, paclitaxel, posaconazole, pralsetinib, regorafenib, ripretinib, ritonavir, lopinavir, paritaprevir revir, ombitasvir, sofosbuvir, ledipasvir, suvorexant, tacrolimus, tadalafil, telaprevir, tolvaptan, vemurafenib, venetoclax, verapamil, and any combination thereof.
[0038] By choosing appropriate conditions, crystallization can be controlled and the undesired growth of crystalline nanoparticles is prevented. Thus, by inducing crystallization under appropriate conditions, the size of amorphous API nanoparticles is not significantly increased.
[0039] In one embodiment, the solution contains one or more surfactants. Exemplary surfactants suitable for the present method are sodium lauryl sulfate (SLS), Tween 80, Tween 20, dioctyl sulfosuccinic acid sodium salt (DOSS), and tocophersolan (TPGS). The total content of the one or more surfactants in the aqueous solution is preferably 0.0025-1.5% by weight. A specific surfactant is SLS. The surfactant enhances wetting efficiency.
[0040] In an exemplary embodiment, the API is budesonide, the polymer is HPMC, and the surfactant, if present, is SLS.
[0041] In another exemplary embodiment, the API is ezetimibe and the copolymer is PVPVA and the surfactant, if present, is SLS.
[0042] In another exemplary embodiment, the API is apalutamide and the copolymer is PVPVA and the surfactant, if present, is SLS.
[0043] In yet another exemplary embodiment, the API is apalutamide and the polymer is HPMC, and the surfactant, if present, is SLS.
[0044] In yet another exemplary embodiment, the API is ceritinib and the polymer is a poloxamer, preferably poloxamer 407, and the surfactant, if present, is SLS.
[0045] In one embodiment, the suspension is dried to provide a solid product comprising the crystalline nano-sized API and one or more polymers and / or copolymers. Drying can be carried out using methods well known in the art. Exemplary drying methods include heating, evaporation, vacuum drying, using a fluidized bed dryer, spray drying, and freeze drying. A specific drying method is evaporation. Grinding the solid product, for example using a mortar, provides a powder suitable for tableting. Grinding does not affect particle size.
[0046] The API can be separated from the wet suspension, for example by filtering using a hydrophilic filter or by centrifuging and then discarding the supernatant containing the polymer and / or copolymer solution. The material can then be washed, for example with water and by repeating the filtering or centrifugation step. This can be repeated as many times as necessary.
[0047] In another aspect of the present disclosure, the present disclosure relates to a process for the preparation of a pharmaceutical dosage form, the process comprising: a) granulating, preferably wet granulating, the crystallized nano-sized API obtained by the process of the present disclosure with one or more pharmaceutical excipients; and b) Compressing the granules Includes.
[0048] The disclosed method allows the preparation of pharmaceutical compositions and oral dosage forms containing relatively high doses of API. Thus, swallowable tablets, i.e. tablets with a total weight not exceeding about 1000 mg but with high drug loads, can be produced. Furthermore, less polymer is required than is required in the corresponding ASD formulation, so the tablet size can be reduced.
[0049] material and method Bulk crystalline ezetimibe (anhydrous, CCDC *:947148), bulk crystalline budesonide, bulk crystalline ceritinib (Form 1), and bulk crystalline apalutamide were purchased from Sinoway Industrial Co, NewChem, MSN Laboratories, and Habotech, respectively. Amorphous nano-sized API was prepared from bulk API using the process disclosed in U.S. Pat. No. 10,098,842. Permeability was tested using a MicroFLUX instrument (Pion Inc.). XRD diffractograms of amorphous nano-sized ezetimibe and amorphous nano-sized budesonide are shown in FIG. 1 for illustration.
[0050] SEM images were taken using a Zeiss Sigma 300 VP SEM instrument. Samples were dispersed in water and filtered through a 0.1 μm filter. The filter was dried, transferred to an SEM sample holder, and coated with a 5 nm thick layer of platinum.
[0051] XRPD measurements were performed using a Malvern PANalytical Empyrean X-ray diffractometer equipped with a Cu Kα (1.54 Å) source, MultiCore optics, and a solid-state PIXcel3D detector. Samples were mounted on aluminum or polycrystalline silicon sample holders using Kapton tape. Dried slurries were measured under Kapton tape without further sample preparation, and suspensions were filtered, dried, and the filter was attached with double-sided tape. Samples were measured in reflection geometry with a spin measurement stage. The measurement range was 5-40 (°2θ). The values of step size and time per step were varied depending on the number of counts per second obtained.
[0052] Dynamic Light Scattering (DLS) measurements were performed using a Malvern Zetasizer. Slurries or dry powders were redispersed in water or 0.1% HPMC (aq.), stirred, and measured after the samples were completely dispersed. A backscattering measurement set-up was used, and the CUMULANTS algorithm was used to obtain the mean particle size (Z-average) and polydispersity index (PI).
[0053] Stability testing The solid material was weighed into individual vials (approximately 150 mg of material each) and transferred to a stability chamber. Three conditions were applied: ambient (material in closed vials at room temperature), 25°C / 65% RH, and 40°C / 75% RH. The material was analyzed at T0, freshly prepared, T7 (7 hours), T14 (14 hours), and T30 (30 days) after the start of the stability study. SEM, XRD, and dissolution / permeability studies were used to evaluate the crystallinity, particle size / morphology, and performance of the material.
[0054] Dissolution Test Dissolution profiles were measured with a Pion Rainbow R2D instrument (Pion Inc UK Ltd, Forest Row, UK). Suspensions were prepared at a concentration of 5 mg / mL in 1% PVPVA suspension vehicle loaded with 40 μg / mL (ezetimibe) or 30 μg / mL (apalutamide). Fasted simulated intestinal fluid (FaSSIF) at pH 6.5 was used for the dissolution study of ezetimibe. Dissolution studies of apalutamide were performed in a biphasic mode starting in simulated gastric fluid (SGF) (0.025 M HCl pH 1.6) for 15 minutes. The contents of the SGF were then converted to FaSSIF medium pH 6.5 by the addition of 10 mL of FaSSIF concentrated medium.
[0055] The temperature was set at 37°C and the stirring speed at 150 rpm. API concentrations were continuously monitored over the path length of a fiber optic UV-Vis probe. UV-Vis spectra were collected at 30 s intervals using a Pion Rainbow Dynamic with either a 10 mm tip for ezetimibe or a 5 mm tip for apalutamide. API concentrations were calculated based on standard curves (5 mg / mL stock solutions of each API in ethanol) using second derivative data transformation in the wavelength range of 293-320 nm for both ezetimibe and apalutamide.
[0056] Transmittance measurement (μFlux) A μFlux device connected to a Rainbow device (Pion Inc UK Ltd, Forest Row, UK) was used to measure the passive permeability of API from different formulations. The suspension was loaded into the donor chamber containing 10 mL of SGF (0.025 M HCl, pH 1.6) and incubated for 15 min. The contents in the donor chamber were then converted to FaSSIF solvent pH 6.5 by adding 10 mL of FaSSIF concentrated solvent and stirring at a speed of 150 rpm. The receiver compartment contained 20 mL of PION acceptor buffer pH 7.4 with a stirring speed of 150 rpm. Permeability was assessed through a gastrointestinal PAMPA membrane (Pion Inc UK Ltd, Forest Row, UK). Suspensions were loaded at either 40 μg / mL for ezetimibe or 30 μg / mL for apalutamide, with suspensions prepared at a concentration of 5 mg / mL in 1 wt.-% PPVVA suspension vehicle. The temperature was set at 37°C during the measurements. UV-Vis spectra were recorded at 30 s intervals at wavelengths of 293-320 nm with either a 10 mm tip for ezetimibe or a 5 mm tip for apalutamide using a Pion Rainbow Dynamic. API concentrations were calculated based on a standard curve (5 mg / mL stock solution in ethanol) using the second derivative to avoid interference from undissolved suspended particles. Standard curves were generated separately for SGF and FaSSIF solvents for the donor chambers and for the acceptor solvent for the acceptor chambers, but the same stock solutions and analytical ranges were used.
[0057] Crystallization measurements The crystallization measurements of API nanoparticles were assessed via suspension kinetic studies. Thus, XRD measurements were performed on the suspensions at different time points. The crystallization reached its thermodynamic maximum when the peak height no longer increased with time.
[0058] Calculations of the polymer and API contents in the suspension were performed as shown in Table 1.
[0059] [Table 1]
[0060] Crystallization Amorphous API nanoparticles (budesonide, ezetimibe, ceritinib, apalutamide) were added as dry powders to aqueous polymer solutions. (i) mixed using a magnetic stirrer and sonicated until the API was completely surrounded by water (wetted). Stirring was continued for 16-24 hours at ambient temperature; or (ii) The mixture was blended using a metal spatula and allowed to stand at room temperature for 18-24 hours.
[0061] The formed suspensions were analyzed after 18-24 hours. SEM and XRD samples were prepared as described above. The results are shown in Table 2.
[0062] Preparation of solid materials The suspension containing nanosized API prepared as shown above was dried overnight in a vacuum desiccator. The solid material was ground to produce a powder. The powder was analyzed by XRD and SEM. The powder containing nanosized API was used for stability, permeability, and dissolution tests as described above. The results are shown in Table 2.
[0063] [Table 2] JPEG2025508347000004.jpg225157 JPEG2025508347000005.jpg225157 JPEG2025508347000006.jpg225157
[0064] Tableting The formulations were manufactured by using wet granulation technique. An API loading of 20% w / w was used and the tablet compression parameters (e.g., die cavity height, compression force, ejection force, strokes / min) were kept constant to study the effect of excipients on tablet properties.
[0065] Compressed tablets may be manufactured by a process which includes the following steps. 1.Wet mixing 2.Wet granulation 3. Drying 4.Crushing and sieving 5. Lubrication 6. Compression 7. Dust removal and storage
[0066] Results and Discussion Figure 2 shows the effect of particle size and morphology on nano-sized amorphous ezetimibe (A) upon crystallization from pure water (B) and from an aqueous solution containing PVPVA (C). As can be seen, crystallization using the method of the present disclosure significantly suppresses particle size growth.
[0067] Figure 3 shows an SEM of the composition of the dried suspension containing ceritinib and 15 wt.-% poloxamer 407. The API:polymer ratio was 1:1. The composition is present as uniform round-like nanoclusters (size less than 3 μm) with nanocrystals of ceritinib ranging from 70 to 110 nm.
[0068] Figure 4 shows the XRD diffractograms of a suspension of ezetimibe in 20 wt.-% aq. PVPVA (API:polymer ratio 1:1) as a function of time. As can be seen, crystal formation can only be observed in the diffractogram after 9 hours of contact.
[0069] SEM images of amorphous nanosized ezetimibe crystallized from aqueous solutions containing three different PPVVA+SLS concentrations are shown in Figure 5. As can be seen, the particle size growth decreased with increasing PPVVA concentration. The crystallinity of samples prepared using aqueous solutions containing 1 wt.-% PPVVA+0.2 wt.-% SLS (a), 2.5 wt.-% PPVVA+0.2 wt.-% SLS (b), and 5 wt.-% PPVVA+0.2 wt.-% SLS (c) was characterized by XRD (Figure 6). Crystalline bulk ezetimibe (d) is shown in the figure as a control. The results indicate that the crystallization of amorphous nanoparticles occurred and that control of crystal size was achieved.
[0070] When PVPVA was replaced by other polymers, the formation of the desired crystalline ezetimibe nanoparticles was significantly reduced. As can be seen from Table 2, the best nanocrystals of ezetimibe were obtained when crystallization was carried out using an aqueous solution containing PVPVA, while the best nanocrystals of budesonide and ceritinib were produced using aqueous solutions containing HPMC and poloxamer, respectively.
[0071] As for apalutamide, the best nanocrystals were produced with PVPVA and HPMC. The XRD patterns of the nanocrystals showed reflections that were not consistent with the polymorphs of apalutamide known in the patent literature to date. This allows us to conclude that a specific molecular arrangement indicates a novel structure of nanocrystalline apalutamide stabilized by HPMC or PVPVA.
[0072] SEM images of budesonide nanoparticles crystallized from aqueous solutions containing three HPMC+SLS concentrations are shown in Figure 7. The crystallinity of these samples was characterized by XRD (Figure 8). The results indicate that crystallization of amorphous nanoparticles occurred and that control of particle size was achieved using HPMC+SLS.
[0073] Crystallization of amorphous APIs can also be performed at higher concentrations, with the limitation that the polymer concentration must also be increased at the same time. This leads to a practical limit of, for example, 5-10 wt.-% for HPMC, but is a viable option for PVPVA. In fact, significantly higher contents, for example up to 50 wt.-%, can be applied in the case of PPVVA.
[0074] As can be seen from Table 2, crystallization can be influenced in particular by the polymer and by the ratio of API to polymer. Typically, the addition of a surfactant, such as SLS, promotes nanocrystallization.
[0075] The stability of nanocrystalline ezetimibe and budesonide prepared according to the present disclosure is summarized in Tables 3 and 4, respectively. As can be seen from the tables, the prepared materials were stable throughout the stability studies. Crystallinity was also confirmed by XRD. XRD diffractograms as a function of time for ezetimibe and budesonide stored at 40° C. / 75% relative humidity are shown as illustrative examples in FIG. 9 and FIG. 10, respectively. SEM images of ceritinib compositions fresh and stored at room temperature for one month are shown in FIG. 11, indicating good stability.
[0076] [Table 3]
[0077] [Table 4]
[0078] Figure 12 shows the FaSSIF and SGF-FaSSIF dissolution profiles of exemplary ezetimibe compositions and bulk ezetimibe compositions of the present disclosure. For the experiments, the compositions as powders were resuspended in an aqueous 1% PPVVA suspension vehicle. As clearly shown, the ezetimibe compositions of the present disclosure have superior solubility to the bulk material, as they dissolve significantly faster under both fasted and fed intestinal conditions.
[0079] Figure 13 shows a comparison of the permeability of ezetimibe compositions prepared according to the present disclosure with the corresponding bulk API. Thus, the permeability of the API of the present disclosure was significantly better than that of the corresponding bulk API.
[0080] The advantage of the present invention compared to amorphous solid dispersions is that it does not require a high content of polymer to stabilize the composition.Furthermore, in contrast to the solvent-antisolvent method, the method of the present disclosure does not involve the use of organic solvents, which may not be completely eliminated by practical manufacturing techniques.In addition, subjecting the API to significant mechanical forces to break bulk API crystals into smaller crystals is avoided.
Claims
1. A method for crystallization of an active pharmaceutical ingredient (API), said method comprising: Providing an amorphous nanosized API; Providing an aqueous solution comprising one or more polymers and / or copolymers; and contacting the amorphous nanosized API with an aqueous solution comprising the one or more polymers and / or copolymers to form a mixture, wherein the content of the amorphous nanosized API in the mixture is higher than the solubility of the amorphous nanosized API in the aqueous solution comprising the one or more polymers and / or copolymers. Including, Thereby a suspension containing nano-sized API in crystalline form is obtained.
2. 2. The method according to claim 1, wherein the content of said amorphous nanosized API in said mixture is at least 10 times higher, preferably at least 50 times higher, more preferably at least 100 times higher, even more preferably at least 500 times higher than the solubility of said amorphous nanosized API in said aqueous solution comprising said one or more polymers and / or copolymers.
3. 3. The method according to claim 1 or 2, wherein the ratio of API:polymer and / or copolymer is from 10:1 to 1:10, preferably from 5:1 to 1:1, wherein the amount of API is calculated as mg / mL of the suspension and the amount of polymer is calculated as % by weight of the one or more polymers and / or copolymers of the suspension.
4. The method according to any one of claims 1 to 3, wherein the aqueous solution comprising the one or more polymers and / or copolymers comprises one or more surfactants.
5. 5. The method according to claim 4, wherein the content of said one or more surfactants in said aqueous solution is from 0.0025 to 1.5% by weight.
6. 6. The method of claim 4 or 5, wherein the one or more surfactants are selected from the group consisting of sodium lauryl sulfate (SLS), Tween 80, Tween 20, dioctyl sulfosuccinic acid sodium salt (DOSS), and tocophersolan (TPGS), preferably SLS.
7. 7. The method of any one of claims 1 to 6, wherein the one or more polymers are selected from the group consisting of polyvinylpyrrolidone / vinyl acetate (PVPVA), polyvinyl acetate (PVA), polyvinylpyrrolidone (PVP), hydroxypropyl methylcellulose (HPMC), hypromellose succinate (HPMCAS), polyacrylic acid (PAA), polyethylene glycol (PEG), polyvinylcaprolactam (PVCL), poloxamer, poly(N-vinylcaprolactam)-poly(vinyl acetate)-poly(ethylene glycol), and proteins.
8. 8. The method of claim 7, wherein the polymer is PVPVA and the aqueous solution contains 0.2 to 50 wt.-% PVPVA, preferably 10 wt.-% to 25 wt.-% PVPVA.
9. 8. The method of claim 7, wherein the polymer is HPMC and the aqueous solution contains 0.2-5 wt.-% HPMC.
10. The method according to any one of claims 1 to 9, wherein the API is selected from BSC class II APIs and BSC class IV APIs.
11. The API is selected from the group consisting of adefovir, dipivoxil, apalutamide, atazanavir, avacopan, deucravacitinib, doravirine, enzalutamide, elagolix, encorafenib, etravirine, everolimus, Etonogestrel, fenofibrate, glecaprevir, pibrentasvir, grazoprevir, pibrentasvir, griseofulvin, telmisartan, itraconazole, ivacaftor, lumacaftor, te Tezacaftor, Elexacaftor, Lonafarnib, Nabilone, Olaparib, Paclitaxel, Posaconazole, Pralsetinib, Regorafenib, Ripretinib, Ritonavir, Lopinavir, Paritaprevir taprevir), ombitasvir, sofosbuvir, ledipasvir, suvorexant, tacrolimus, tadalafil, telaprevir, telmisartan, tolvaptan, vemurafenib, venetoclax, verapamil,The method according to any one of claims 1 to 10, selected from the group consisting of:
12. The method of any one of claims 1 to 11, wherein said contacting comprises mixing said suspension.
13. The method of any one of claims 1 to 12, wherein said contacting comprises subjecting said suspension to ultrasound.
14. The intensity of the ultrasonic wave is 3 W / cm 2 14. The method of claim 13, wherein:
15. The method of any one of claims 1 to 14, wherein said contacting is performed for at least 10 hours, preferably at least 16 hours, more preferably at least 24 hours.
16. 16. The method according to any one of claims 1 to 15, comprising drying the suspension and thereby producing a solid comprising the nano-sized API in crystalline form and the one or more polymers and / or copolymers.
17. 17. The method of claim 16, comprising grinding the solid and thereby producing a powder comprising the nano-sized API in crystalline form and the one or more polymers and / or copolymers.
18. 18. The method according to any one of claims 1 to 17, comprising separating the nano-sized API in crystalline form from the suspension, and optionally drying the separated nano-sized API in crystalline form.
19. The method according to any one of claims 1 to 18, wherein the particle size of the crystalline API is not more than 300% larger, preferably not more than 100% larger, more preferably not more than 50% larger, even more preferably not more than 25% larger, and most preferably not more than 10% larger than the particle size of said amorphous nano-sized API.
Citation Information
Patent Citations
Method for producing strip from hot-rolled rod
JP1998512198A
Synthesis, cap formation, and dispersion of nanocrystals
JP2014503446A
Preparations, manufacturing methods, and uses of hydrophobic therapeutic agents
JP2015520149A
Process for the preparation of crystalline nano-particle dispersions
US20050202092A1
Nanocrystal production method and nanocrystal production device
WO2017014314A1